Electroporation-Based CRISPR/Cas9 Mosaic Mutagenesis of β-Tubulin in the Cultured Oyster - Chan, Jiulin; Zhang, Wei; Xu, Yue; Xue, Yu; Zhang, Linlin (Frontiers in Marine Science, 2022)
Genome editing using CRISPR/Cas9 is enabling genetics improvement of productive traits in aquaculture. Previous studies have proven CRISPR/Cas9 to be feasibility in the oyster, one of the most cultured shellfish species. Here, we applied electroporation-based CRISPR/Cas9 knockout of β-tubulin and built a highly efficient genome editing system in the Crassostrea gigas angulate. We identified the β-tubulin gene in the oyster genome and showed its spatio-temporal expression patterns by analyzing RNA-seq data and larval in situ hybridization. We further designed multiple highly specific guide RNAs (sgRNAs) for its coding sequences. Long fragment deletions were detected in the mutants by agarose gel electrophoresis screening and further verified by sanger sequencing. In addition, the expression patterns of Cgβ-tubulin in the trochophore peritroch and intestinal cilia cells were altered in the mutants. Scanning electron microscopy represented shortened and almost complete depleted cilia at the positions of peritroch and the posterior cilium ring in Cgβ-tubulin mosaic knockout trochophores. Notably, there was a significant decrease in larval swimming behavior in the mutants by motility assay. These results demonstrate that β-tubulin is sufficient to mediate cilia development and swimming behavior in oyster larvae. By applying Cgβ-tubulin as a marker genes, our study established electroporation-based CRISPR/Cas9 mosaic mutagenesis as an efficient methods for gene function studies in the oyster. Moreover, our research also provides a powerful tool for genetic engineering breeding to improve productive traits in oysters and other aquaculture species.